2016
DOI: 10.1097/mat.0000000000000359
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation Incidence, Characteristics, and Outcomes in Neonatal Down Syndrome Patients

Abstract: Practice patterns for extracorporeal membrane oxygenation (ECMO) use in newborns with Trisomy 21 (T21) have not been fully reported. The goals of this study were to 1) determine the incidence of ECMO use in T21 neonates; 2) identify clinical and demographic characteristics associated with ECMO use in this population; 3) describe outcomes of neonates with T21 supported with ECMO. This was a retrospective cohort study using the Pediatric Health Information System database (January 2000 to January 2014). Given th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Race and/or ethnicity was the primary study aim in five citations (13%). No statistical difference or mixed results were observed in 25 (64%) of studies (51, 52, 135–147). Studies with cardiac disease, arrest, transplant, or shock observed patients from diverse backgrounds having lower ECMO use in seven (28, 31, 129, 148–151) versus higher ECMO use in three (26, 89, 152).…”
Section: Resultsmentioning
confidence: 86%
“…Race and/or ethnicity was the primary study aim in five citations (13%). No statistical difference or mixed results were observed in 25 (64%) of studies (51, 52, 135–147). Studies with cardiac disease, arrest, transplant, or shock observed patients from diverse backgrounds having lower ECMO use in seven (28, 31, 129, 148–151) versus higher ECMO use in three (26, 89, 152).…”
Section: Resultsmentioning
confidence: 86%
“… 38 Neonates with DS more frequently require mechanical ventilation and extracorporeal membrane oxygenation (ECMO; needed in 2.3% of neonates with DS in 1 study of 5737 newborns in 43 centers across the United States). 40 …”
Section: Resultsmentioning
confidence: 99%
“…As stated before, patients with DS have multiple medical issues, especially cardiac and respiratory (9,14,20), that usually need to be addressed in the pediatric time period. Significant pulmonary hypertension or recovery from cardiac surgery place the pediatric DS population at a higher risk for ECMO use (17,21,22). By the time these patients reach adulthood, these issues have likely abated, been minimized with treatment, or no longer require major cardiac surgery such that the risk for ECMO use is significantly less than in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal membrane oxygenation (ECMO) is a form of mechanical support that may be used to support patients with refractory respiratory or cardiac failure. ECMO use has been described for neonates and pediatric patients with DS who are severely ill (17)(18)(19)(20)(21)(22). Pediatric patients with DS appear to have increased prevalence of ECMO support compared to the general population (22).…”
mentioning
confidence: 99%